Physical performance of Finnish futsal players, analysis of game intensity and fatigue in official futsal games - Vähäkoitti, Ville (2017)
Introduction. Futsal has grown notably in last years and have over 12 million players worldwide. Futsal is a high-intensity indoor sport where burst of multi-planar movements varies with short periods of rest. Futsal is played on a court sized 40 x 20 m for two halves of 20 min, where clock is stopped when ball is out of play. Purpose of this study was to find out physical performance of Finnish futsal players and analyse intensity and fatigue in official futsal games. Methods. Two Finnish Futsal League teams were involved (n = 19), age 26.3 (± 3.0 years), body mass 76.4 (± 6.2 kg), height 178.7 (± 5.7 cm), BMI 23.9 (± 1.4 kg/m2) and body fat % 12.3 (± 4.0 %). Measurement were done in the middle of the season 2016-2017, during two months’ period. Two games from both teams were analysed. Measuring included physical performance tests (sprint test 5-m and 20-m, agility test, CMJ, isometric leg press and maximal treadmill running test) and game measurements (HR, movement distances and velocities, playing time, accelerations and deceleration). CMJ and lactate were measured before, middle and after futsal game to assess fatigue. Results. Sprint times were 1.03 (± 0.04 s) in 5-m and 3.01 (± 0.07 s) in 20-m. Agility test time was 6.87 (± 0.25 s). CMJ result was 41.8 (± 5.6 cm) and isometric leg press 5327 (± 1070 N). In the maximal treadmill running test HRmax was 191.6 (± 9.5 bpm), VO2max 59.8 (± 5.4 ml/kg/min) and VEmax 171.9 (± 20.8 l/min). Futsal players moved on average 4463.0 (± 1169.3 m) on intensity 54.0 (± 13.2 m/min) during the futsal games. Sprinting occurred on average 39.7 (± 17.2) times in the games. HRmax achieved during the futsal games was 191.6 (± 9.9 bpm), and average HR 147.0 (± 16.9 bpm). Fatigue did not occur during or after the futsal games when measured as CMJ or lactate (p > 0.05). Conclusions. From the results of the physical performance tests, it seems that Finnish futsal player’s physical fitness is comparable to play futsal in high level. During Finnish Futsal League games the distance moved is similar to those measured in literature, but the intensity lower when expressed as % HRmax, distance moved in one minute or in different speed zones. Because fatigue was not evident during the games, higher-intensity tactic or less substitutions to the key players could be used. In general, consistency in research methods would ease comparison of different studies. More futsal research is needed to understand the fundamentals of the sport that is growing and evolving constantly.